Integrating hydrogeomorphological concepts in management approaches of lowland agricultural streams: Perspectives, problems and prospects based on case studies in Quebec. Issue 1 (2nd January 2017) - Paradis, Alexandre; Biron, Pascale M.
Abstract : Alternative management approaches for agricultural streams based on hydrogeomorphological principles such as a two-stage channel are promising, but need to be further tested in contexts other than the Midwestern United States. In Quebec (Canada), the presence of many deep drain outlets may limit their applicability. The objectives of this research are to (1) assess the feasibility of implementing the two-stage channel design in Quebec; (2) determine how alternative management approaches compare with traditional management from an economical point of view, and (3) evaluate the impact of modifying the drain outlet design using small horseshoe wetlands to accommodate hydrogeomorphological adjustments of the channel. A combination of case studies and numerical modelling (HEC-RAS, Hydrologic Engineering Center's River Analysis System) was used for three study sites located in the Montérégie region (QC). Based on regional hydraulic geometry curves, additional space on each bank required for a two-stage channel ranged between 1.3 and 2.8 m for a width equal to 3 times the inset channel. Hydraulic modelling confirms previous findings of improved drainage capacity at high flow, (up to a 54% increase). Cost analysis reveals that two-stage and over-widened channels are 3 to 4 times more expensive to implement when compared to traditional trapezoidal clean-out dredging operations, mainly due to spoil removal and transportation. However, self-formed channels are less expensive since they only require additional riparian land. A crop yield analysis in the near-stream zone at three sites which are frequently flooded revealed markedly lower productivity in zones within the flooding space. The horseshoe wetland design for drain outlets could also be maintained at low cost, and would promote more heterogeneity than the traditional trapezoidal ditches. Using alternative agricultural stream management approaches based on hydrogeomorphological concepts would be feasible in the Quebec context without compromising the overall productivity of this key economic sector.